Effects of training and exhaustive exercise on the mitochondrial oxidative capacity of brown adipose tissue. Issue 11 (November 1984) - Gohil, K.; Henderson, S.; Terblanche, S. E.; Brooks, G. A.; Packer, L.
Abstract : Oxidation of pyruvate, α-ketoglutarate, palmitoylcarnitine, succinate, and ferrocytochrome c by interscapular-brown-adipose-tissue (BAT) mitochondria of untrained and trained rats were measured at rest and alter running to exhaustion. At rest, BAT mitochondria from trained rats showed significantly lower activities (<50%) for the oxidation of all the substrates. In untrained rats the activities of the enzymes for the oxidation of all the substrates except pyruvate and succinate were lower at exhaustion compared to the resting state when expressed on a per-gram-fresh-Weight basis. In trained rats all of the enzyme activities increased as a result of exhaustive exercise. These differences between the two groups of rats in the post-exercise changes in oxidative capacities suggest that following an initial adaptation, resulting in a large decrease in mitochondrial oxidative activity, training protects the residual oxidative pathways against exercise-induced inactivation. These data show that unlike exposure to cold, or overfeeding, a physiological stimulus such as exercise reduces the oxidative capacity of BAT, and therefore may reduce the thermogenic activity of the tissue in endurance-trained rats as has been addressed in the scientific literature.